Ethiopia Alive & Thrive Endline Survey 2014: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data for the endline part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions (CBI), delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of infant and young child feeding (IYCF) practices in two regions where the integrated family health program (IFHP) operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative funded by the Bill & Melinda Gates Foundation to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The impact evaluation of the A&T Ethiopia community-based intervention and mass media activities includes the 2010 baseline and 2014 endline surveys and a smaller-scale 2013 process evaluation survey. Together, these studies generate answers to one of the major learning objectives for the overall initiative: how A&T interventions achieve their impact. The Ethiopia endline survey applied five separate questionnaires that aimed to capture elements along the program impact pathways. These instruments included a household questionnaire, a community questionnaire and 3 frontline health workers questionnaires. The Ethiopia endline household survey aimed at detecting changes in three age-specific indicators: (1) rates of exclusive breastfeeding (EBF) among infants 0-5.9 months of age; (2) complementary feeding (CF) practices among children 6-23.9 months of age; and (3) stunting prevalence among children 24-59.9 months of age. The same two-stage cluster sampling method for selecting households applied at baseline was used for the endline survey. After random sampling and selection of households across three sampling frames: children aged 0-5.9 months (n=619), 6-23.9 months (n=875), and 24-59.9 months (n=1475) for the three age groups, an oversample of all additional households with children aged 24-35.9 months (n=727) were included in the endline survey to improve the reliability of stunting estimates.